(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to identify the psychological well-being of the educational counselors, as well as to identify the significance of differences in psychological well-being according to the variables (gender, duration of service). The number of scale’s items reached (42) items distributed evenly on six dimensions (autonomy, environmental mastery, personal growth, positive relationships with others, purpose in life, self-acceptance), for each field (7) items. The scale was applied to a sample of (400) school counselors (male-female) who were randomly selected from the six directorates in the Baghdad governorate for the academic year 2020/2021. The results showed that the educational counselors in the Baghdad governorate for the six directorates have psychological well-being. There are no statistically significant differences in psychological well-being between males and females and duration of service among counselors.